FILSAFAT PANCASILA DALAM PENDIDIKAN DI INDONESIA MENUJU BANGSA BERKARAKTER - Khairunnisa Khairunnisa; Kholid Junaidi; May Tiara Saputri; Octavia Dalimunthe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The philosophy of Pancasila plays a crucial role in education in Indonesia as a foundation for building national character. Pancasila serves not only as the state ideology but also as a moral guide that can shape the behavior and attitudes of the younger generation. In the context of education, the application of Pancasila's values is expected to create individuals with integrity, responsibility, and a love for their homeland. Pancasila-oriented education encourages students to think critically, appreciate differences, and contribute positively to society. Through strengthening character education based on Pancasila, it is hoped that a generation capable of facing global challenges will emerge without losing their national identity. However, challenges in the implementation of Pancasila in education still exist, such as the lack of a deep understanding of Pancasila's values among educators and students. Therefore, systematic efforts are needed in designing the curriculum and developing effective teaching methods to instill Pancasila's values. Thus, the philosophy of Pancasila can become a strong foundation for education in Indonesia, ultimately producing a character-driven, tolerant nation ready to face the dynamics of modern development.